Nationhood at work : an ethnography of workplaces in Montreal and Brussels - Poitras, Dave (Cultures of society, 2019)
How are nations (continued to be) made? In this important contribution to nationalism studies, Dave Poitras explores how nationhood and the idea of living in a world of nations are experienced in the cities of Montreal and Brussels. Drawing on ethnographic research, he identifies three typical ways of enacting nationhood, thereby capturing the various dynamics through which non-political actors "do nationhood". In particular, Poitras explores the question of marginalization in bi-ethnonational milieus, demonstrating how bi-ethnicity is hegemonic in Brussels and Montreal because it is legitimized by individuals' everyday activities